Surgical Intervention in Gastric Carcinoid is Associated With Improved Survival in Local and Regional Disease. (September 2018) - Callahan, Ann F.; White, Michael; Ituarte, Philip; Gagandeep, Singh; Woo, Yanghee; Fong, Yuman; Melstrom, Laleh
Abstract : Introduction: Gastric carcinoid is a rare entity with complex management options. This study aims to determine if surgical intervention in patients with local, regional, and metastatic gastric carcinoid is associated with prolonged survival. Materials and Methods: The California Cancer Registry merged with the California Office of Statewide Health Planning and Development was queried for patients with a diagnosis of gastric carcinoid (2000 to 2011). Clinicopathologic characteristics, management, and outcomes were evaluated. Results: There were 1012 patients with a diagnosis of gastric carcinoid identified. The median age was 63 (range, 18 to 99) and the majority of patients were women (615, 60.7%). Most patients had localized disease (644, 64%), whereas 9.4% (95) had regional and 13.4% (133) had distant metastases at diagnosis. The majority of patients underwent gastric surgery (56.7%, n=574 vs. 43.2%, n=438). Prolonged survival was associated with gastric surgery in patients with both local (median survival not reached; P< 0.0001) and regional disease (27 mo with surgery vs. 5 mo with no surgery; P =0.0007). In patients who underwent gastrectomy and resection of hepatic metastasis, the survival approached those patients who had surgery for only regional disease (26 vs. 27 mo, P =0.8721). Conclusions: Although the biology of the disease is the most significant predictor of overall outcome, when technically feasible and where comorbidities allow, aggressive endoscopic or surgical intervention should be offered for local and locoregional diseases, respectively.